When Is Osteonecrosis Not Osteonecrosis?: Adjudication of Reported Serious Adverse Joint Events in the Tanezumab Clinical Development Program. Issue 2 (February 2016) - Hochberg, Marc C.; Tive, Leslie A.; Abramson, Steven B.; Vignon, Eric; Verburg, Kenneth M.; West, Christine R.; Smith, Michael D.; Hungerford, David S.
Abstract : Objective: Tanezumab, a monoclonal antibody against nerve growth factor, has demonstrated efficacy in clinical trials of chronic pain in osteoarthritis (OA) and chronic low back pain. Unexpected adverse events (AEs) described as osteonecrosis (ON) occurred during tanezumab development, leading the US Food and Drug Administration to impose a partial clinical hold for all indications except cancer pain. A blinded Adjudication Committee (AC) including orthopedic surgeons, rheumatologists, and an orthopedic pathologist reviewed and adjudicated joint‐related AEs in the tanezumab clinical program. Methods: The AC adjudicated all reported cases of ON as well as cases of total joint replacements (TJRs) not reported as ON for which radiographs obtained within 9 months of the surgery were available. The AC prespecified categories for joint safety events including primary ON, worsening OA (rapid progression of OA [RPOA], normal progression of OA, insufficient information to distinguish between rapid and normal progression of OA), other, or insufficient information to distinguish between primary ON and worsening OA or another diagnosis. Results: The AC reviewed events in 249 of 386 patients with an investigator‐reported AE of ON and/or a TJR. Two events were adjudicated as primary ON, 200 events were adjudicated as worsening OA (68 of which were classified as RPOA), 29 events had another diagnosis, 11 had insufficient information to distinguish primary ON from worsening OA, and 7 did not have committee member consensus. Conclusion: Despite initial reports, tanezumab treatment was not associated with an increase in ON but was associated with an increase in RPOA. Higher doses of tanezumab, tanezumab administered with nonsteroidal antiinflammatory drugs, and preexisting subchondral insufficiency fractures were risk factors for RPOA in this cohort.